The Influence of Cyclic and Isothermal Hot Corrosion on Nickel-Based Superalloy - Doleker, Kadir Mert; Karaoglanli, A.C. (TÜBİTAK, 2020)
Nickel-based superalloys have a wide range of usage area such as gas turbines, nuclear reactors, generators. They are especially preferred in areas where mechanical strength and corrosion resistance are important. Hot corrosion is a highly corrosive type of damage in high temperature applications. In hot corrosion, molten salts easily react with reactive components, causing premature damage to the workpieces. In this study, Inconel 718 was subjected to hot corrosion tests as a nickel-based superalloy. 50% V2O5-50% Na2SO4 mixtures were used as corrosion salt. Cyclic and isothermal hot corrosion tests were carried out at 900 ° C for 18 hours. Corrosion products and microstructural changes formed in Inconel 718 were characterized by scanning electron microscopy (SEM), SEM-Energy Dispersive X-Ray (EDX), SEM-mapping and X-Ray Diffraction (XRD) analysis after hot corrosion tests. At the end of the isothermal and cyclic hot corrosion tests, Inconel 718, which has been subjected to cyclic hot corrosion, has been found to be more affected by the damage. Similar results were observed in terms of the corrosion products and the damage mechanism. © 2020, TUBITAK. All rights reserved.
Çevrimli ve İzotermal Sıcak Korozyonun Nikel Esaslı Süper Alaşım Malzemeye Etkisi
Keywords: Hot Corrosion; Inconel 718; Molten Salt; Na2SO4; V2O5